Pro Kontra Ujian Nasional - H. Fajri Ismail (LPPM IAIN Sorong, 2015)
The study is conducted to determine the relationship of coping with the anxiety level of students in the national exams. This study uses descriptivecorrelative design involving 153 respondents taken by simple random sampling technique. The results shows that 109 respondents experience high anxiety and 87 respondents use adaptive coping in dealing with the problem. The results areas follows. 1) The learning mastery of Economics subjects in public high schools is 76.91% (“very good”), the learning mastery of Economics subjects in private high schools is 75.89% (“good”); the level of learning mastery of Economics lesson is “good”, 75.97% in public and 70.58% in private high schools; the level of Accounting lesson is “very good”, 78.78% in public and 86.51% in private high schools; the material in the Accounting lesson with the lowest rate in public and private high schools is “to describe financial statement and its calculation”; the difficult materials in Economics lesson in public high schools are “to describe macro and micro economy or problems faced by the government in the financial sector”, “to describe opportunity cost” and “to describe price index/inflation”; the difficult materials in the Economics lesson in private high schools are “to describe price index/inflation”, “to describe security/security mechanism exchange”, “to describe APBN/APBD, income and spending of government sources, “to describe the ways how to develop cooperation”. 2) The utilization of the NE results by teachers in public high schools is relatively better than that in private high schools, and therefore the utilization of the NE results by teachers need to be increased; the kind of utilization are to give a lot of excercises and to engage student in evaluating their assignments and exercises. This article elaborates pro and contra opinion about national examination